Early and Mid-Term Postoperative Outcome of Inflammatory Abdominal Aortic Aneurysms - Prifti, Edvin; Nuellari, Edmond; Esposito, Giampiero; Krakulli, Klodian; Kapedani, Edmond (The Thoracic and Cardiovascular Surgeon, 2015)
Introduction and Objectives The aim of this study is to report our experience on the postoperative outcome of surgical treatment of inflammatory abdominal aortic aneurysm (IAAA).Materials and Methods Between January 1997 and March 2014, 35 patients with IAAA underwent surgery. The mean age was 63 ± 18 years. Chronic renal failure was identified in 11 (31.4%) patients, and ischemic heart disease was confirmed in 15 (43%) patients. The mean aortic aneurysm diameter was 68 ± 25 mm. The abdominal aorta was clamped above the renal arteries in 6 (17%) patients.Results The hospital mortality was 5.7% (2 patients). Three patients developed an aortic pseudoaneurysm and underwent reoperation. Another patient developed a femoral anastomotic pseudoaneurysm 7 years after operation, which was treated surgically. The overall reoperation-free actuarial survival at 1, 5, and 7 years was 94, 62, and 50%, respectively. The Cox model revealed the delta erythrocyte sedimentation rate (p = 0.002), ischemic heart disease (p = 0.006), and renal failure (p = 0.036) as strong predictors for poor overall outcome.Conclusion Early postoperative outcome in terms of mortality and morbidity seems acceptable; however, patients with IAAA have an increased risk for reoperation due to pseudoaneurysm formation. Strong predictors for poor overall outcome seem to be elevated erythrocyte sedimentation rate, ischemic heart disease, and chronic renal failure.
Keywords: inflammatory aneurysm; aorta; surgery; abdominal; surgery